2011
DOI: 10.1007/s10750-011-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of two Spartina species in phytostabilization and bioaccumulation of Co, Cr, and Ni in the Tinto–Odiel estuary (SW Spain)

Abstract: Vascular plants in salt marshes strongly influence processes of heavy metal accumulation. Many studies have focused on this issue; however, there is a lack of information regarding the effects of plants on the distribution of certain poorly studied metals, such as Co, Cr, and Ni. The aim of this study was to comparatively evaluate the capability of Spartina densiflora Brongn. and Spartina maritima (Curtis) Fernald, to accumulate Co, Cr, and Ni and influence the sediment composition around their roots, investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…With respect to TF, it was below the unit for all elements in all sites, except for Fe in site 5sa (Table 8). This pattern suggests an avoidance of metal translocation, keeping the metals in roots and surrounding sediments, accordingly to previous studies performed in different Spartina species (Windham et al 2003;Duarte et al 2009;Cambrollé et al 2011;Almeida et al 2011). Possible physiological mechanisms responsible for restricted uptake and translocation within plants include cell wall immobilization, complexation with substances such as phytochelatins, and barriers at the root endodermis (Vale et al 1990;Clements et al 2002;Mucha et al 2005;Anjum et al 2013).…”
Section: Resultssupporting
confidence: 82%
“…With respect to TF, it was below the unit for all elements in all sites, except for Fe in site 5sa (Table 8). This pattern suggests an avoidance of metal translocation, keeping the metals in roots and surrounding sediments, accordingly to previous studies performed in different Spartina species (Windham et al 2003;Duarte et al 2009;Cambrollé et al 2011;Almeida et al 2011). Possible physiological mechanisms responsible for restricted uptake and translocation within plants include cell wall immobilization, complexation with substances such as phytochelatins, and barriers at the root endodermis (Vale et al 1990;Clements et al 2002;Mucha et al 2005;Anjum et al 2013).…”
Section: Resultssupporting
confidence: 82%
“…While below-ground structures reflected the soil metal concentration pattern, this was not so evident in above-ground concentrations. These results are consistent with findings of previous studies, which found that different Spartina species, including S. densiflora, minimize the translocation of trace metals to the photosynthetic tissues (Reboreda et al, 2008;Cambrollé et al, 2008Cambrollé et al, , 2011Duarte et al, 2010;Curado et al, 2014;Idaszkin et al, 2014b). It has been showed that when potentially toxic elements are taken up, plants may avoid toxicity in the above-ground parts by restricting the translocation from below-ground structures, effective re-translocation of the element from the above-ground parts back to the below-ground where they may be accumulated or even excreted (Weis and Weis, 2004;Redondo-Gómez, 2013).…”
supporting
confidence: 93%
“…While several studies have recorded higher metal concentration in soils associated to Spartina maritima roots than in soils without roots (Caçador et al, 1996;Reboreda and Caçador, 2007;Reboreda et al, 2008). Cambrollé et al (2008Cambrollé et al ( , 2011 found this pattern in the Odiel marsh (SW Spain), but not in the Tinto marsh (SW Spain).…”
mentioning
confidence: 85%
“…These have either reported the effects of metal toxicity on Spartina alterniflora in greenhouse studies (Mendelssohn et al 2001, Mateos-Naranjo et al 2008 or have examined metal accumulation in the field at polluted sites (Cambrollé et al 2011, Salla et al 2011. Across these studies, S. alterniflora was highly tolerant of soil metal contamination, able to hyperaccumulate metals, and capable of phytoremediation (Salla et al 2011).…”
Section: Foliar Metal Concentrationmentioning
confidence: 99%